Home based negative pressure wound therapy and moist dressing in the treatment of diabetic foot ulcers - Basheer, Shiraz; Kannanavil, Naseef; Rajendran, Sunil (International Surgery Journal, 2019)
Background: Negative pressure wound therapy (NPWT) is a non-invasive wound closure system that uses controlled, localized negative pressure to help heal chronic and acute wounds. The objective of the present study was to compare home based NPWT and moist wound dressing in home care setting with respect to wound healing and time taken for healing among diabetic ulcer patients and the comparison of cost involved for the treatment. Methods: A hospital based prospective observational study where all patients were presented to the Department of Surgery at MES Medical College with diabetic ulcer between 1st January 2016 and 30th March 2017 were included in the study; ulcer size and surface area were measured using vernier calipers and Wagner’s grade between the two groups were evaluated at the time of enrollment. Results: Complete ulcer healing by primary intention was achieved in 86.8% in home based NPWT group vs. 44.3% in conventional moist dressing group. Average duration taken for healing in home based NPWT patient was 3.03 months and in moist dressing group was 4.58 months. Split skin grafting was needed in 2 patients in HB-NPWT group vs. 7 in moist dressing group. 9.3 hospital visits in HB-NPWT group vs 136.8 sessions in moist dressing group. Conclusions: The present study states that NPWT is superior to conventional moist dressing for the management of chronic diabetic foot ulcers. Cost is approximately 1/10th of standard NPWT.